Characterization of aluminium pad under different process conditions - Wang, Jian Hua. (2008)
The objective of this study is to improve the aluminum film uniformity by optimizing the process condition. The aluminum film was deposited by a sputtering process on 200mm wafers in AMAT Endura® PVD chambers.